THE RELATIONSHIP BETWEEN BLOOD PRESSURE AND PUPIL TO LIMBUS DIAMETER RATIO IN HYPERTENSIVE WOMEN: A PILOT STUDY - R, Archana; Sailesh, Kumar Sai; Bashetti, Srilatha; Mishra, Soumya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: This study was undertaken to observe the relationship between blood pressure (BP) and pupil to limbus diameter (PLD) ratio in hypertensive working women. Methods: A total of 30 hypertensive working women were part of the study after obtaining written, voluntary, informed consent, and ensuring confidentiality. PLD ratio was measured by two-box method as described in the literature. Results: Positive correlation was observed between PLD ratio of the right eye (r=0.951) and left eye (r=0.927) and systolic BP. This correlation is statistically significant at 0.01 levels (two tailed). Positive correlation was observed between PLD ratio of the right eye (r=0.844) and left eye (r=0.828) and diastolic BP. This correlation is statistically significant at 0.01 levels (two tailed). Positive correlation was observed between PLD ratio of the right eye (r=0.416) and left eye (r=0.396) and pulse pressure. This correlation is statistically significant at 0.05 levels (two tailed). Positive correlation was observed between PLD ratio of the right eye (r=0.883) and left eye (r=0.844) and mean arterial BP. This correlation is statistically significant at 0.05 levels (two tailed). Positive correlation was observed between PLD ratio of the right eye (r=0.841) and left eye (r=0.819) and pulse rate. This correlation is statistically significant at 0.05 levels (two tailed). Conclusion: Positive correlation was observed between PLD ratio and autonomic parameters. We recommend further detailed studies to utilize the measurement of PLD ratio as an autonomic function test.